Translation and cross-cultural adaptation of the Malay version of the painDETECT Questionnaire - Loh, Huai Heng; Anne, Yee; Shanty, Velaiutham; Zanariah, Hussein; Mohamad Zaki, Mohd Amin; Sharifah Aishah, Wan; Tong, Chin Voon; Sim, Chun Yang; Linda Then, Yee Yen; Mohamad Fairuz, Ali; Mohammad Arif, Shahar; Kuan, Yueh Chien; et al. (ASEAN Neurological Association (ASNA), Asian & Oceanian Association of Neurology (AOAN), 2023)
Background: The painDETECT questionnaire (PDQ) is a useful tool for screening of patients with neuropathic pain. This study aimed to translate the PDQ into the Malay language (PDQ-M) and to achieve cross-cultural adaptation of the questionnaire for use in Malaysia. Methods: The translation and cultural adaptation process of the English version of PDQ was performed based on international guidelines. Subsequently, 97 patients with neuropathic and nociceptive pain based on clinician’s diagnoses were recruited to complete three-type numeric rating scale (NRS) of pain followed by PDQ-M. Results: On the basis of cognitive debriefing, several changes of the translated PDQ-M were made. A total of 53 patients with neuropathic pain and 44 with nociceptive pain (54.6% females, 45.4% males, mean age 52.4 years ± 14.2) were recruited into this study. The most common class of analgesia prescribed for patients with neuropathic pain was anti-convulsant, whereas co-analgesic therapy, which includes NSAID and COX-2 inhibitor, was the most prescribed for patients with nociceptive pain. Combination analgesia was used in 32.1% of those with neuropathic pain, and 11.4% of patients with nociceptive pain. The median time taken for respondents to complete the questionnaire was 420 seconds. In regression analysis, active smoking (beta 0.586, p<0.001) and female gender (beta -0.422, p=0.008) were associated with higher PDQ-M scores only among those with neuropathic pain. Conclusions: The Malay version of the painDETECT questionnaire was translated and cross-culturally adapted for ease of understanding among the local population via careful face-to-face interview.